Home » Simplify log10 a(frac{1}{3}) + (frac{1}{4})log10 a – (frac{1}{12})log10a7

Simplify log10 a(frac{1}{3}) + (frac{1}{4})log10 a – (frac{1}{12})log10a7

Simplify log10 a(frac{1}{3}) + (frac{1}{4})log10 a – (frac{1}{12})log10a7
  • A.
    1
  • B.
    (frac{7}{6})log10 a
  • C.
    zero
  • D.
    10
Correct Answer: Option C
Explanation

log10 a(frac{1}{3}) + (frac{1}{4})log10 a – (frac{1}{12})log10a7 = log10 a(frac{1}{3}) + log10(frac{1}{4}) – log10 a(frac{7}{12})
= log10 a(frac{7}{12}) – log10 a(frac{7}{12})
= log10 1 = 0